Genome-wide association study of SNP- and gene-based approaches to identify susceptibility candidates for lupus nephritis in the Han Chinese population - Song, Kangkang; Zheng, Xiaodong; Liu, Xiaomin; Sheng, Yujun; Liu, Lu; Wen, Leilei; Shang, Shunlai; Deng, Yiyao; Ouyang, Qing; Sun, Xuefeng; Li, Qinggang; Chen, Pu; et al. (Frontiers in Immunology, 2022)
Background: Lupus nephritis (LN) is one of the most common and serious complications of systemic lupus erythaematosus (SLE). Genetic factors play important roles in the pathogenesis of LN and could be used to predict who might develop LN. The purpose of this study was to screen for susceptible candidates of LN across the whole genome in the Han Chinese population. Methods: 592 LN patients and 453 SLE patients without renal damage were genotyped at 492,970 single nucleotide polymorphisms (SNPs) in the genome-wide association study (GWAS). Fifty-six SNPs were selected for replication in an independent cohort of 188 LN and 171 SLE without LN patients. Further quantitative real-time (qRT) PCR was carried out in 6 LN patients and 6 healthy controls. Gene-based analysis was conducted using the versatile gene-based test for GWAS. Subsequently, enrichment and pathway analyses were performed in the DAVID database. Results: The GWAS analysis and the following replication research identified 9 SNPs showing suggestive correlation with LN (P<10-4). The most significant SNP was rs12606116 (18p11.32), at P=8.72×10−6. The qRT-PCR results verified the mRNA levels of LINC00470 and ADCYAP1, the closest genes to rs12606116, were significantly lower in LN patients. From the gene-based analysis, 690 genes had suggestive evidence of association (P<0.05), including LINC00470. The enrichment analysis identified the involvement of transforming growth factor beta (TGF-β) signalings in the development of LN. Lower plasma level of TGF-β1 (P<0.05) in LN patients and lower expression of transforming growth factor beta receptor 2 in lupus mice kidney (P<0.05) futher indicate the involvement of TGF-β in LN. Conclusions: Our analyses identified several promising susceptibility candidates involved in LN, and further verification of these candidates was necessary.